Latissimus Dorsi with Immediate Fat Transfer Flap versus Deep Inferior Epigastric Perforator Flaps for Autologous Breast Reconstruction: A Retrospective Comparison of 400 Patients - Varis, Eveliina (My University, 2026)
Breast reconstruction is a procedure that is commonly used after mastectomy. Nowadays, autologous tissue use has become the cornerstone for breast reconstruction. In this study, we compared two methods of autologous breast reconstruction: the fat-augmented latissimus dorsi flap (FALD) and the deep inferior epigastric perforator flap (DIEP). The purpose of this study was to evaluate and compare postoperative outcomes and overall complication rates between FALD and DIEP breast reconstruction techniques. This retrospective study compared outcomes of FALD and DIEP reconstruction in 400 patients treated at Turku University Hospital between 2009 and 2024. Of these, 130 patients underwent FALD reconstruction and 270 underwent DIEP reconstruction. Demographic data, operative details and postoperative complications were analyzed. The overall complication rates were similar between the two groups. DIEP reconstructions had longer operative times, hospital stays, and wound healing issues. Immediate contralateral symmetrization and seromas were more frequent in the FALD group. Both techniques demonstrated comparable safety profiles. While the DIEP flap remains the gold standard for autologous breast reconstruction, FALD procedures may offer a less complex postoperative course. Moreover, FALD provides a viable autologous option for surgeons without microsurgical expertise or access to microsurgical facilities.
Keywords: Rintarekonstruktio; LD-rekonstruktio; DIEP-rekonstruktio; postoperatiivinen komplikaatio